The inclination toward funding cash waqf-based education: evidence from Kuwait Waqf Public Foundation - Meshari Al-Daihani (STIM LASHARAN JAYA MAKASSAR, 2021)
Kuwait Awqaf Public foundation plays a vital role in supporting Community development in Kuwait. However, it is undeniable that support for the educational forums by Kuwait Awqaf public foundation (KAPF) is significantly low graded compared to other distribution channels of Waqf. Besides, the literature that discussed the factors influencing behavioral intention to Waqf giving behavior is extremely limited in Kuwait. Therefore, this study aims to investigate the factors influencing behavral intention to endow to the education sector, particularly among the employees of Kuwait Awqaf public foundation (KAPF), based on the theory of planned behavior (TPB). A set of questionnaires was constructed to measure the validity of the theory in the field of Waqf giving behavior in Kuwait. This study found that all variables attitude, subjective norms, and perceived behavioral control were significantly related to intention to contribute to the education sector by Waqf in Kuwait.